2014
DOI: 10.1002/jmri.24742
|View full text |Cite
|
Sign up to set email alerts
|

Mechatronic system for in-bore MRI-guided insertion of needles to the prostate: An in vivo needle guidance accuracy study

Abstract: This system provides a reliable method of accurately aligning needle guides for in-bore transperineal needle delivery to the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, poor visualization of the tumor and time constraints during the ablation procedure may result in errors in placing the needle at its intended location. Inaccurate placement of the needles with respect to the tumor may lead to repeated needle insertions or incomplete treatment if the error is not detected. Errors in needle placement may be reduced by the use of MRI visible needles or needle tips .…”
Section: Discussionmentioning
confidence: 99%
“…However, poor visualization of the tumor and time constraints during the ablation procedure may result in errors in placing the needle at its intended location. Inaccurate placement of the needles with respect to the tumor may lead to repeated needle insertions or incomplete treatment if the error is not detected. Errors in needle placement may be reduced by the use of MRI visible needles or needle tips .…”
Section: Discussionmentioning
confidence: 99%
“…A reproducible reduction of the intervention time to less than three hours would make greater use of focal therapy in the clinical routine more realistic. MR-compatible robotic systems for automated intervention control could contribute to this [49].…”
Section: Instruments and Operating Concepts For Oncologymentioning
confidence: 99%
“…Certain MRI-guided robotic systems have progressed through clinical trials in animals or humans such as [23], [10], [1], [21]. Nevertheless, due to the formidable cost of MRI which is proportional to the imaging duration, the accumulated evidence and lessons from those clinical trials have revealed that it is imperative to minimize procedure time and thus reduce cost [21] to facilitate widespread adoption of this technique in additional hospitals.…”
Section: Introductionmentioning
confidence: 99%